Novel Antibacterial Agents: An Emergent Need to Win the Battle Against Infections - Simoes, Natercia G.; Bettencourt, Ana F.; Monge, Nuno; Ribeiro, Isabel A.C. (Mini Reviews in Medicinal Chemistry, 2017)
Background: Multiple strategies have been recommended for prevention and control of antibacterial resistance. Solutions will need to be found soon if we are not to run the serious risk of losing the ability to treat bacterial infections, especially the ones arising from multi-resistant strains. Deep knowledge of the resistance mechanisms followed by novel therapeutic drugs and vaccines are needed. A consolidated, multidisciplinary and regulated strategy is required by this challenge. Objective: This review will be focused on new strategies to control infections. Among strategies to tackle antibiotic resistance that have been under investigation, are the use of antimicrobial peptides, phage therapy and phage enzymes, therapeutic antibodies, quorum sensing inhibitors and, finally, the antibacterial nanomedicines. Although all of the approaches seem to be effective, and at least one of them has been in use for relatively a long time (phage therapy), antibacterial nanomedicines show the most diverse range of different approaches regarding potential translation to clinics. Results & Conclusion: Several advances have been made but a great effort is still mandatory in order to reach feasible, effective and marketable novel antimicrobial products.
Keywords: monoclonal antibodies